High-Performance Process Improvement - Pastinen, Markus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
High-performance process improvement takes process improvement to the next ambition level. The kernel of the substance is a generic process improvement process that operates under the strictest time, quality and cost constraints. Thanks to a modular composition and robust methods the scope may range from one single person to networks with hundreds of companies. This is realized via three high-class phases: network and company analysis and synthesis process analysis and synthesis the implementation, including process improvement education and training and the practical realization of the improvement potential The presented methods contain mass customization features and a very advanced logic for optimizing the interaction of people, technology, information and material both in the process improvement process itself and the focus process. The book is based on an extensive R&D effort and thorough practical verifications in more than 75 companies in almost any business and in all sizes.
High-Performance Process Improvement Fundamentals -- High-Performance Process Improvement Concepts -- Design Concepts of the High-Performance Process Improvement Process -- Network and Company Analysis and Synthesis -- Process Analysis and Synthesis -- The Implementation -- Derivative Concepts and Future Outlines.
Keywords: Economics; Industrial management; Business planning; Economics/Management Science; Organization/Planning.; Management/Business for Professionals; Business/Management Science, general